2020
DOI: 10.3390/w12123495
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution Characteristics of Reference Evapotranspiration in Shandong Province from 1980 to 2019

Abstract: Reference evapotranspiration (ET0) is an important part of the water cycle and energy cycle during crop growth. Understanding the influencing factors and spatiotemporal variations of ET0 can guide regional water-saving irrigation and regulate agricultural production. Data for daily meteorological observations of temperature, relative humidity, wind speed, and sunshine hours from 38 surface meteorological stations were used to analyze the spatiotemporal variations and trends in Shandong Province from 1980 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
1
5
1
Order By: Relevance
“…Moreover, most of the previous studies are focused in the dryland areas where water availability primarily restrains ecosystem development, and atmospheric demand is usually high with high variabilities due to the high seasonal radiation and low vegetation covers (Hua et al, 2020); yet less is known about the variations of ET p and its connections with vegetation and soil water content in the humid areas. In a previous study in Guangdong, a humid southern province of China, it was found that ET p has decreased by ∼1 mm yr −1 during the water years of 2002-2014 (Zhou et al, 2021), comparable to other studies in some dry areas despite different study periods (Yang et al, 2011;Wang et al, 2014;Zhang et al, 2020). Given the role of ET p in the hydrologic cycles, it is important to assess comprehensively the variations of ET p and its influencing factors, especially the interaction with surface conditions.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, most of the previous studies are focused in the dryland areas where water availability primarily restrains ecosystem development, and atmospheric demand is usually high with high variabilities due to the high seasonal radiation and low vegetation covers (Hua et al, 2020); yet less is known about the variations of ET p and its connections with vegetation and soil water content in the humid areas. In a previous study in Guangdong, a humid southern province of China, it was found that ET p has decreased by ∼1 mm yr −1 during the water years of 2002-2014 (Zhou et al, 2021), comparable to other studies in some dry areas despite different study periods (Yang et al, 2011;Wang et al, 2014;Zhang et al, 2020). Given the role of ET p in the hydrologic cycles, it is important to assess comprehensively the variations of ET p and its influencing factors, especially the interaction with surface conditions.…”
Section: Introductionsupporting
confidence: 80%
“…Additionally, the change rate over 2005-2015 was greater than that over 1982-2004 for nearly all variables, which indicates that in the recent decade or so, the climate activities are enhanced(Yang et al, 2018) and the region gets drier and warmer in terms of rising temperature and reduced humidity, precipitation and soil water content. Down to seasons, ET p was highest in summer and lowest in winter, different from that in a province in north China(Zhang et al, 2020). The changes in ET p and the environmental variables presented different seasonal features, e.g., rainfall and SWC increased only in summer, different from the result in Pearl River basin during 1961-2007 byGemmer et al (2011); meanwhile, R s increased in spring and winter while decreased in summer and autumn; ETp and NDVI increased in all seasons and higher increase rate was in spring and winter.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…The closer the correlation coefficient is to 1 or −1, the stronger the correlation is; the closer the correlation coefficient is to 0, the weaker the correlation is Ref. [22].…”
Section: Pearson Correlationmentioning
confidence: 99%
“…A shortage of water is the most serious problem in this area. In addition, the research on the influence factors of ET mostly focuses on meteorological factors [ 25 , 26 ], and there is a lack of in-depth research on the influence of surface parameters on ET.…”
Section: Introductionmentioning
confidence: 99%